Development of Traditional Bun Arrangement Module for 11th Grade Students in State Vocational High School - Siti Fauziah Lubis; Ellizar Ellizar; Sukardi Sukardi (BIRCU, 2019)
The problem in this study is the completeness of student learning in traditional bun arrangement subjects is still unsatisfactory, students lack the initiative to find information about traditional bun arrangement to support learning, students lack understanding of the basic topic oftraditional bun arrangement, students are less skilled in making traditional bun arrangement techniques and the limitations time and resources for learning during learning activities in the delivery of traditional bun arrangement.Based on these problems, this study aims to develop a valid, practical and effective discovery learning module based on subjects in traditional bun arrangement. This development model plompis applied. There are three phase, namely initial investigation, prototyping and assessment. The evaluation method used is formative evaluation consisting of self evaluation, expert review, individual evaluation, and small group evaluation. The research instruments used were interview sheets, questionnaires in the form of validity in practicality sheet and objective. Validation results obtained as very high criteria. The practical results by students in small group and on field test obtained as high criteria, while the level of practicality by teachers obtained as very high. The result of hypothesis test show that there was a significant difference between the studentslearning outcomes of the experimental and the control class in the school. The result shows that the traditional bun arrangement module based on discovery learning has fulfilled the valid, practical and effective criteria.